RISK FACTORS OF THE ERECTILE DYSFUNCTION IN THE PATIENTS WITH CARDIOVASCULAR DISEASES - E. V. Minakov; R. A. Khokhlov; T. N. Kuznetsova; Y. V. Popovskaya; D. V. Snustikov; E. E. Tsareva; V. I. Yarliykova; N. M. Akhmedzhanov (Рациональная фармакотерапия в кардиологии)
Aim. To study erectile dysfunction prevalence among out-patients with arterial hypertension (HT) and/or coronary heart disease (CHD) as well as to study risk factors of erectile dysfunction.Material and methods. The anonymous poll was carried out among 103 male patients with HT and/or CHD. General information about patient, medical history, treatment was analyzed. All patients were examined by cardiologists. Erectile function was assessed with The International Index Erectile Function (IIEF) questionnaire.Results. 86 (84%) questionnaires were returned. 62 (72%) patients from 86 responding had erectile dysfunction. Age, blood pressure level, abdominal obesity, beta-blocker therapy and chronic heart failure affected erectile function.Conclusion. The erectile dysfunction was common disorder among male patients with HT and/or CHD. Early erectile dysfunction diagnosis, prevention and therapy are necessary to provide high level of compliance in patients with cardiovascular diseases.